2007
DOI: 10.1021/la0634286
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of the Orientations of Thermotropic Liquid Crystals to Protein Binding Events at Lipid-Decorated Interfaces

Abstract: We report a study of the interactions of proteins with monolayers of phospholipids (D/L-alpha-dipalmitoyl phosphatidylcholine and L-alpha-dilauroyl phosphatidylcholine) spontaneously assembled at an interface between an aqueous phase and a 20-microm-thick film of a nematic liquid crystal (4'-pentyl-4-cyanobiphenyl). Because the orientation of the liquid crystal is coupled to the organization of the lipids, specific interactions between phospholipase A2 and the lipids (binding and/or hydrolysis) that lead to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
132
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 56 publications
3
132
0
3
Order By: Relevance
“…Recent reports have demonstrated that it is also possible to tailor the interfaces of LCs at aqueous interfaces in ways that lead to changes in the orientational order of the LCs. For example, recent studies on thin films of supported LCs have demonstrated that orientational ordering transitions in LCs can be triggered by the presence of lipids, [1,8,13,14] surfactants, [15][16][17] proteins, [3,18,19] and viruses. [10,20] These changes in orientational order arise from coupling between the aliphatic tails of the adsorbed amphiphiles and the mesogens of the LCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have demonstrated that it is also possible to tailor the interfaces of LCs at aqueous interfaces in ways that lead to changes in the orientational order of the LCs. For example, recent studies on thin films of supported LCs have demonstrated that orientational ordering transitions in LCs can be triggered by the presence of lipids, [1,8,13,14] surfactants, [15][16][17] proteins, [3,18,19] and viruses. [10,20] These changes in orientational order arise from coupling between the aliphatic tails of the adsorbed amphiphiles and the mesogens of the LCs.…”
Section: Introductionmentioning
confidence: 99%
“…The nature and extent of these changes is influenced by the structure of the amphiphiles (e.g., tail length or head group structure) [15,17] or by chemical or physical events in the aqueous phase that disrupt or perturb these assemblies (such as the binding or enzymatic action of a protein). [18,19] Additionally, LC-based reporting offers potential advantages over conventional techniques because it does not require complex instrumentation or labels (enzymatic or fluorescent).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the liquid crystal acts as an amplifi er for molecular binding events. [ 10 ] Note, however, that past research in this area has been limited to reporting the adsorption of biomaterials at LC interfaces, including biological toxin, [ 11 ] proteins, [ 12 ] and stem cells. [ 13 ] In this work we go beyond that, and demonstrate that LCs can serve as faithful reporters of distinct molecular motifs, such as the alpha helices or beta sheets of protein aggregates.…”
mentioning
confidence: 99%
“…Over incubation for 2 h, a monolayer of L-DLPC was laden at LC-aqueous interface and resulted in a complete anchoring transition from planar to homeotropic alignment ( Figure 5(d)). Aside from lipids [29,30], it has been shown that amphiphilic molecules, such as surfactants [31][32][33][34][35][36][37] and polymers [38][39][40][41] at these interfaces are strongly coupled to the ordering of the LCs, and the presence and organization of these molecules can be reported through changes in the optical appearance of the LCs. It was noted that LCs are fluid-like and possess mobility, combined with liquid crystallinity, assembling biological amphiphiles at the LC-aqueous interface promises a possibility for mimicking cell membrane, which is mobile and composed of a large amount of lipids in liquid crystalline phase.…”
Section: Lc-aqueous Interfacesmentioning
confidence: 99%